Observation of the foreign protein expression in the yeast cell by using the enhanced cyan fluorescent protein - Hoang, Nguyen Duc; Thuoc, Tran Linh; Ueda, Mitsuyoshi; Tanaka, Atsuo (Academia Journal of Biology, 2015)
We have successfully constructed two plasmids pC-Z-Ste and pZ-C-Ste, which express a fusion protein containing the ECFP (Enhanced Cyan Fluorescent Protein) and the protein A encoded by the Z gene on the cytoplasmic side of the plasma membrane of Saccharomyces cerevisiae MT8-1. The oligonucleotide encoding the C-terminal 9 amino acids of the Ste18p protein was cloned downstream of the genes encoding the fusion proteins in order to anchor the fusion proteins on the cytoplasmic side of the plasma membrane. A GS linker was used between the fusion protein and the C-terminal of the Ste18p protein for minimizing the interaction among themselves. The Z gene was cloned upstream or downstream of the ECFP gene in order to examine whether the protein A at C terminal or N terminal of CFP affects the expression of the fusion protein. These two plasmids were sequenced to check the inframe between the gene ECFP, Z and the C terminal Ste. Under the control of the GAPDH (glyceraldehyde 3-phosphate dehydrogenase) promoter, the expression of the fusion proteins ECFP-Protein A or Protein A-ECFP in the yeast cell could be confirmed by the fluorescent microscope.